Method for regulating and controlling friction coefficient of carbon-based thin film through friction-induced sliding interface reconstruction
By depositing the transition group metal intermediate layer and the transition group metal carbide reinforcement layer on the surface of the carbon-based film, and forming the transition group metal oxide transfer film through friction treatment, the problem of large fluctuations in the friction coefficient of the hydrogen-free carbon-based film is solved, and the problem of large fluctuations in the friction coefficient of the hydrogen-free carbon-based film is achieved. Carbon-based films have low friction and high wear resistance under extreme conditions.
Patent Information
- Application Number
- CN202411567621.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-07
AI Technical Summary
In the changing working environment, the existing hydrogen-free carbon-based films cause strong adhesion of the sliding interface formed between the film and the dual material to fluctuate greatly, and are very susceptible to external factors such as temperature, humidity and sliding. The influence of speed and other factors makes it difficult to achieve stable and controllable tribological behavior.
By depositing transition group metal intermediate layer and transition group metal carbide enhancement layer on the surface of the carbon-based thin film, and excited the nanocrystals for oxidation reaction through friction treatment, a transition group metal oxide transfer film is formed, thereby building a low shear force and weak The sliding interface of adhesion characteristics realizes adaptive regulation of the friction coefficient of carbon-based film.
The friction coefficient of the carbon-based film is significantly reduced, and its durability and stability under extreme operating conditions are improved, especially in low humidity conditions.
Smart Images

Figure CN119392200A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of regulating the friction coefficient of carbon-based films, and in particular to a method for regulating the friction coefficient of a carbon-based film by reconstructing a friction-induced sliding interface. Background Art
[0002] With the rapid development of industrial equipment, the demand for efficient and long-life operation of mechanical parts under extreme working conditions is increasing. In this context, materials with excellent tribological properties have become the frontier research focus of advanced materials science. Tribological performance is not only directly related to the operating efficiency and energy consumption of mechanical systems, but also greatly affects the service life of parts. Therefore, how to develop materials with both low friction and high wear resistance has become a topic of common concern in academia and industry. Hydrogen-free carbon-based films have gradually become a research hotspot in the field of solid lubricating materials due to their excellent performance in friction and wear resistance, especially the potential application prospects under harsh conditions have made them attract much attention.
[0003] The tribological properties of hydrogen-free carbon-based films mainly rely on the synergistic effect of two major mechanisms: "graphitization of the sliding interface caused by friction" and "passivation of suspended carbon bonds under the influence of environmental humidity". Specifically, during the friction process, the amorphous structure of the hydrogen-free carbon-based film is gradually transformed into an ordered graphite layer under the action of local high temperature and high pressure, forming a low-shear lubrication layer on the sliding interface, which significantly reduces the friction coefficient. At the same time, in a humid environment, the active carbon bonds suspended on the surface of the carbon-based film undergo a passivation reaction with the moisture in the environment to generate a stable low-energy surface, further reducing the interfacial adhesion effect, thereby improving the wear resistance of the film. These physical and chemical changes work synergistically to enable hydrogen-free carbon-based films to exhibit good tribological properties.
[0004] However, in the changing working environment, the friction coefficient of existing hydrogen-free carbon-based films fluctuates greatly due to the strong adhesion of the sliding interface formed between the film and the dual material caused by friction. It is easily affected by external factors such as temperature, humidity and sliding speed, making it difficult to achieve stable and controllable tribological behavior. Under harsh conditions of low humidity or high-speed sliding, hydrogen-free carbon-based films are more prone to significant wear and shortened service life, which seriously limits their reliable application in harsh working environments. The tribological properties of existing hydrogen-free carbon-based films often rely on the inherent chemical composition and structural design of the material, and their tribological behavior is mainly dominated by the strong adhesion sliding interface. However, the inherent limitations of this sliding interface make it difficult to significantly reduce its friction coefficient, limiting the possibility of further optimizing friction performance. Summary of the invention
[0005] The purpose of the present invention is to provide a method for regulating the friction coefficient of a carbon-based film by reconstructing a friction-induced sliding interface, constructing a sliding interface with excellent self-lubricating properties, giving the carbon-based film excellent tribological properties under low humidity conditions, greatly reducing the friction coefficient, and achieving a further breakthrough in the low friction of the carbon-based film.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for regulating the friction coefficient of a carbon-based film by friction-induced sliding interface reconstruction, which is characterized by comprising the following steps:
[0008] (1) pre-treating the substrate, and then performing a first sputtering to deposit a transition metal intermediate layer on the surface of the pre-treated substrate;
[0009] (2) using carbon and transition metal carbide as sputtering targets respectively, performing a second sputtering on the surface of the transition metal intermediate layer obtained in step (1) to obtain a transition metal carbide reinforced carbon-based film;
[0010] (3) A friction dual material ball is used to perform friction treatment on the surface of the transition metal carbide reinforced carbon-based film obtained in step (2), so as to stimulate the transition metal carbide nanocrystals to undergo an oxidation reaction to form oxidation products, and simultaneously drive the oxidation products to sieve and migrate, spontaneously construct a transition metal oxide transfer film, thereby constructing a sliding interface with low shear force and weak adhesion characteristics, and realizing the regulation of the friction coefficient of the carbon-based film by friction-induced sliding interface reconstruction.
[0011] Preferably, the pretreatment in step (1) comprises: polishing the substrate, ultrasonic degreasing and Ar + Ion cleaning is performed to obtain a pretreated substrate.
[0012] Preferably, in step (1), the transition metal intermediate layer is a Cr or Ti layer; and the thickness of the transition metal intermediate layer is 180 to 240 nm.
[0013] Preferably, the transition metal carbide in step (2) is at least one of tungsten carbide and titanium carbide.
[0014] Preferably, the second sputtering conditions in step (2) are: using unbalanced magnetron sputtering technology, the pressure is 2×10 -3 ~5×10 -3 Pa, the substrate pulse bias is -50 to -100 V, the frequency is 200 to 350 kHz, the argon pressure is 0.1 to 0.6 Pa, the power of the transition metal carbide target is 0 to 500 W, and the power of the carbon target is 1500 to 2500 W.
[0015] Preferably, in step (2), the thickness of the transition metal carbide reinforced carbon-based film is 2-3 μm, and the average particle size of the transition metal carbide nanocrystals in the transition metal carbide reinforced carbon-based film is 1-10 nm.
[0016] Preferably, the friction dual material ball in step (3) is a GCr15 ball or an Al 2 O 3 ball; the roughness of the friction dual material ball is 0.05-0.2 μm; the Rockwell hardness of the friction dual material ball is 60-80.
[0017] Preferably, during the friction treatment in step (3), the oxygen partial pressure in the environment is 20% to 50%, and the relative humidity of the environment is 5% to 50%; the temperature of the friction system of the friction treatment is 20 to 35°C.
[0018] Preferably, the load of the friction treatment in step (3) is 10 to 15N.
[0019] Preferably, during the friction treatment in step (3), the sliding frequency of the friction dual material ball is 1 to 7 Hz, the sliding reciprocating distance of the friction dual material ball is 3 to 7 mm, and the friction treatment time is 30 to 60 min.
[0020] The present invention provides a method for regulating the friction coefficient of a carbon-based film by friction-induced sliding interface reconstruction. First, a transition metal intermediate layer is deposited on a pretreated substrate surface as a bonding layer, carbon and transition metal carbide are used as sputtering targets respectively, and the conditions of the second sputtering are adjusted to obtain a carbon-based film containing transition metal carbide nanocrystals of different sizes (i.e., transition metal carbide reinforced carbon-based film), and then a friction treatment is performed. The friction-induced sliding interface reconstruction is used to accurately regulate the tribological behavior of the carbon-based film, and the multiple effects of external factors (such as oxygen partial pressure, temperature, humidity, load, sliding frequency, friction dual material, etc.) on the friction coefficient are controlled, and the evolution law of the sliding interface microstructure during the friction process is combined. During the friction treatment process, the transition metal carbide nanocrystals are stimulated to undergo an oxidation reaction to form oxidation products, and the oxidation products are simultaneously driven to be sieved and migrated, and a transition metal oxide transfer film is spontaneously constructed. Finally, under the friction treatment, the sliding interface reconstruction is achieved, and a sliding interface with low shear force and weak adhesion characteristics is constructed, thereby achieving adaptive regulation of the friction coefficient of the carbon-based film. The method provided by the present invention not only significantly reduces the friction coefficient of the carbon-based film, but also greatly improves the durability and stability of the carbon-based film under extreme working conditions; especially in a low-humidity atmospheric environment, during the above-mentioned friction treatment process, the transition metal carbide nanocrystalline particles in the carbon-based film are induced by friction heat and stress, and gradually undergo oxidation reactions to generate corresponding oxidation products (i.e., oxides), which are gradually transferred to the dual surface through the selective migration of the friction interface to form a continuous and stable transfer film. The transfer film interacts with the graphitized layer on the surface of the film to construct a sliding interface with excellent self-lubricating properties. It is this interface reconstruction mechanism that gives the carbon-based film excellent tribological properties under low humidity conditions, greatly reduces the friction coefficient, and enhances the wear resistance and stability of the carbon-based film. In addition, the method provided by the present invention provides a new theoretical support and practical basis for achieving ultra-low friction performance of carbon-based films. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The friction coefficient variation trend diagram of the corresponding transition metal carbide reinforced carbon-based film during the friction treatment process described in Example 1 of the present invention and Comparative Example 1;
[0022] Figure 2 The friction coefficient variation trend diagram of the corresponding transition metal carbide reinforced carbon-based film during the friction treatment process described in Examples 2 to 4 of the present invention and Comparative Examples 2 and 3, wherein: Figure 2 The small and medium figures are the corresponding curves of load and average friction coefficient;
[0023] Figure 3The friction coefficient variation trend diagram of the corresponding transition metal carbide reinforced carbon-based film during the friction treatment process described in Examples 5 to 9 of the present invention;
[0024] Figure 4 It is a three-dimensional morphology of the wear spot on the surface of the GCr15 ball during the friction treatment process of the corresponding transition metal carbide reinforcement in Example 5 of the present invention, wherein Y represents the longitudinal position information on the measurement plane, and X represents the lateral position information on the measurement plane;
[0025] Figure 5 is a cross-sectional SEM image of the WC / aC film in Example 1 of the present invention;
[0026] Figure 6 This is a surface SEM image of the WC / aC film in Example 2 of the present invention. DETAILED DESCRIPTION
[0027] The present invention provides a method for regulating the friction coefficient of a carbon-based film by friction-induced sliding interface reconstruction, comprising the following steps:
[0028] (1) pre-treating the substrate, and then performing a first sputtering to deposit a transition metal intermediate layer on the surface of the pre-treated substrate;
[0029] (2) using carbon and transition metal carbide as sputtering targets respectively, performing a second sputtering on the surface of the transition metal intermediate layer obtained in step (1) to obtain a transition metal carbide reinforced carbon-based film;
[0030] (3) A friction dual material ball is used to perform friction treatment on the surface of the transition metal carbide reinforced carbon-based film obtained in step (2), so as to stimulate the transition metal carbide nanocrystals to undergo an oxidation reaction to form oxidation products, and simultaneously drive the oxidation products to sieve and migrate, spontaneously construct a transition metal oxide transfer film, thereby constructing a sliding interface with low shear force and weak adhesion characteristics, and realizing the regulation of the friction coefficient of the carbon-based film by friction-induced sliding interface reconstruction.
[0031] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art.
[0032] The present invention pre-treats the substrate and then performs the first sputtering to deposit a transition metal intermediate layer on the surface of the pre-treated substrate.
[0033] In the present invention, the material of the substrate is preferably at least one of AISI 304 stainless steel, 41CrAlMo74 alloy structural steel and AISI 316L stainless steel.
[0034] In the present invention, the pretreatment comprises: polishing the substrate, ultrasonic degreasing and Ar+ Ion cleaning is performed to obtain a pretreated substrate.
[0035] In the present invention, the polishing is preferably diamond paste polishing; the roughness of the substrate surface after polishing is 0.02 μm to 0.04 μm; the ultrasonic degreasing treatment is preferably ultrasonically performed with acetone for 10 to 20 minutes. + Ion cleaning is preferably performed with Ar at a base pulse bias voltage of -450 to -600 V. + The ions are cleaned for 10 to 20 minutes. The present invention improves the cleanliness and flatness of the substrate surface through pretreatment, providing high-quality attachment conditions for subsequent processes.
[0036] In the present invention, the transition metal intermediate layer is a Cr or Ti layer; the thickness of the transition metal intermediate layer is preferably 180 to 240 nm, more preferably 190 to 22 nm. The present invention deposits the transition metal intermediate layer on the substrate surface as an adhesion layer to improve adhesion.
[0037] In the present invention, the first sputtering condition is preferably: using unbalanced magnetron sputtering technology, the pressure is 2 to 5×10 -3 Pa, substrate pulse bias voltage is -50 to -100 V, frequency is 200 to 350 kHz, argon pressure is 0.1 to 0.6 Pa, and power of transition metal target is 700 to 900 W. The present invention controls the conditions of the first sputtering within the above range to ensure uniformity and bonding strength of the film layer, and improve the density and performance stability of the coating.
[0038] After the transition metal intermediate layer is deposited, the present invention uses carbon and transition metal carbide as sputtering targets respectively, performs a second sputtering on the surface of the transition metal intermediate layer, and obtains a transition metal carbide reinforced carbon-based film;
[0039] In the present invention, the carbon is at least one of graphite and carbon black; the transition metal carbide is at least one of tungsten carbide and titanium carbide.
[0040] In the present invention, the second sputtering conditions are preferably: using unbalanced magnetron sputtering technology, the pressure is 2 to 5×10 -3Pa, substrate pulse bias is -50 to -100 V, frequency is 200 to 350 kHz, argon pressure is 0.1 to 0.6 Pa, power of transition metal carbide target is 0 to 500 W, and power of carbon target is 1500 to 2500 W. The present invention controls the conditions of the second sputtering within the above range to optimize the structural uniformity of the film and improve the hardness, wear resistance and adhesion of the film. In addition, the present invention controls the power of the transition metal carbide target and the power of the carbon target within the above range to adjust the different sizes of the transition metal carbide nanocrystals of the prepared carbon-based film, thereby adjusting the mechanical properties of the film to adapt to different mechanical or thermal environment requirements.
[0041] In the present invention, the thickness of the transition metal carbide reinforced carbon-based film is preferably 2 to 3 μm; the average particle size of the transition metal carbide nanocrystals in the transition metal carbide reinforced carbon-based film is preferably 1 to 10 nm. The present invention controls the thickness of the transition metal carbide reinforced carbon-based film and the average particle size of the transition metal carbide nanocrystals within the above range to ensure that the film has excellent mechanical properties and wear resistance, optimizes structural uniformity, and thus exhibits excellent comprehensive performance in various harsh environments.
[0042] After obtaining the transition metal carbide reinforced carbon-based film, the present invention uses a friction dual material ball to perform friction treatment on the surface of the transition metal carbide reinforced carbon-based film, stimulates the transition metal carbide nanocrystals to undergo an oxidation reaction to form oxidation products, and simultaneously drives the oxidation products to screen and migrate, spontaneously constructing a transition metal oxide transfer film, thereby constructing a sliding interface with low shear force and weak adhesion characteristics, and realizing the regulation of the friction coefficient of the carbon-based film by friction-induced sliding interface reconstruction.
[0043] In the present invention, the friction dual material ball is preferably a GCr15 ball or an Al 2 O 3 ball; the roughness of the friction dual material ball is preferably 0.05 to 0.2 μm; the Rockwell hardness of the friction dual material ball is preferably 60 to 80; the diameter of the friction dual material ball is preferably 3 to 8 mm, more preferably 6 mm.
[0044] In the present invention, during the friction treatment process, the oxygen partial pressure in the environment is preferably 20% to 50%, and the relative humidity of the environment is preferably 5% to 50%; the temperature of the friction system of the friction treatment is preferably 20 to 35°C, and the load of the friction treatment is preferably 10 to 15N. In the present invention, during the friction treatment process, the sliding frequency of the friction dual material ball is preferably 1 to 7Hz, the sliding reciprocating distance of the friction dual material ball is preferably 3 to 7mm, and the time of the friction treatment is preferably 30 to 60min. During the friction treatment process, the present invention controls the oxygen partial pressure and relative humidity in the environment, the friction system temperature, the load, the sliding frequency and the time of the friction treatment within the above ranges to optimize the surface properties of the film and ensure that the ideal tribological properties are achieved under controlled friction conditions.
[0045] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] Example 1
[0047] A method for regulating the friction coefficient of a carbon-based film by friction-induced sliding interface reconstruction, comprising the steps of:
[0048] (1) AISI 304 stainless steel substrates were machined into 30 mm × 30 mm × 3 mm sizes and then polished with different grades of diamond paste to obtain a surface roughness Ra of 0.03 μm. They were then ultrasonically degreased with acetone for 15 min and heated with Ar at a substrate pulse bias of -500 V. + The ions were cleaned for 20 min to obtain a pretreated substrate, and then a first sputtering was performed to deposit a Cr intermediate layer with a thickness of 210 nm on the surface of the pretreated substrate;
[0049] The first sputtering conditions are: using unbalanced magnetron sputtering technology, the pressure is 3×10 -3 Pa, substrate pulse bias voltage is -70 V, frequency is 250 kHz, argon pressure is 0.2 Pa, and power of Cr target is 800 W;
[0050] (2) performing a second sputtering on the surface of the Cr intermediate layer obtained in step (1) to deposit a WC / aC film (i.e., a transition metal carbide reinforced carbon-based film) having a thickness of 2.3 μm and a WC nanocrystal size of 2.6 nm;
[0051] The second sputtering conditions are: using unbalanced magnetron sputtering technology, the pressure is 3×10-3 Pa, substrate pulse bias voltage is -70 V, frequency is 250 kHz, argon pressure is 0.2 Pa, power of tungsten carbide target is 240 W, power of carbon target is 2500 W;
[0052] (3) A friction test was conducted using a CSM reciprocating friction and wear tester produced by Anton Paar, and a friction dual material ball was used to perform friction treatment on the surface of the WC / aC film obtained in step (2) to stimulate the WC nanocrystals to undergo an oxidation reaction to form WO 3 , and simultaneously drive WO 3 The sieve migrated to the surface of the dual steel ball and spontaneously constructed a WO-rich 3 Transfer film, thereby constructing a sliding interface with low shear force and weak adhesion characteristics, and realizing the regulation of the friction coefficient of the carbon-based film through friction-induced sliding interface reconstruction;
[0053] The friction dual material ball is a GCr15 ball with a roughness of 0.1 μm, a Rockwell hardness of 62, and a diameter of 6 mm;
[0054] During the friction treatment process, with the help of a high-precision atmosphere control system, the oxygen partial pressure in the environment is adjusted to 50% (oxygen atmosphere), the temperature of the friction system is strictly controlled at 25° C., the relative humidity of the environment is adjusted to 30%, the load is maintained at 10N, the sliding frequency of the friction dual material ball is adjusted to 5Hz, the sliding reciprocating distance of the friction dual material ball is 5mm, and a constant load loading mode is adopted to achieve WO 3 The effective screening transfer; the friction treatment time is 30min, ensuring the rich WO 3 The continuity and integrity of the transfer film formation.
[0055] Comparative Example 1
[0056] A WC / aC film was prepared and its friction coefficient was adjusted according to the method of Example 1. The difference from Example 1 was that during the friction treatment process, the oxygen partial pressure in the environment was adjusted to 0% (i.e., nitrogen atmosphere) with the help of a high-precision atmosphere control system.
[0057] The tribological behavior of the WC / aC film during the friction treatment process described in Example 1 and Comparative Example 1 was tested using the CSM reciprocating friction and wear tester produced by Anton Paar, and the corresponding friction coefficient variation trend diagram was obtained as shown in FIG. Figure 1 As shown. Figure 1It can be seen that the friction coefficient of the WC / aC film in the oxygen atmosphere with an oxygen partial pressure of 50% described in Example 1 can reach 0.05, while the friction coefficient in the nitrogen atmosphere described in Comparative Example 1 is as high as 0.2. And in the entire friction stage of the rubbing treatment process, the friction coefficient of the WC / aC film in the oxygen atmosphere drops sharply after a short running-in period, and the friction coefficient tends to be stable after 900 seconds; while the friction coefficient in the nitrogen atmosphere shows violent fluctuations. In the oxygen atmosphere described in Example 1, a uniform and dense WO-rich surface is formed on the surface of the dual steel ball rubbed with the WC / aC film with a WC nanocrystal size of 2.6nm. 3 Transfer film.
[0058] Example 2
[0059] A method for regulating the friction coefficient of a carbon-based film by friction-induced sliding interface reconstruction, comprising the steps of:
[0060] (1) AISI 304 stainless steel substrates were machined into 30 mm × 30 mm × 3 mm sizes and then polished with different grades of diamond paste to obtain a surface roughness Ra of 0.03 μm. They were then ultrasonically degreased with acetone for 15 min and heated with Ar at a substrate pulse bias of -500 V. + The ions were cleaned for 20 minutes to obtain a pretreated substrate, and then a first sputtering was performed to deposit a transition metal intermediate layer Cr layer with a thickness of 210 nm on the surface of the pretreated substrate;
[0061] The first sputtering conditions are: using unbalanced magnetron sputtering technology, the pressure is 3×10 -3 Pa, substrate pulse bias voltage is -70 V, frequency is 250 kHz, argon pressure is 0.2 Pa, and power of Cr target is 800 W;
[0062] (2) performing a second sputtering on the surface of the Cr intermediate layer obtained in step (1) to deposit a WC / aC film (i.e., a transition metal carbide reinforced carbon-based film) having a thickness of 2.3 μm and a WC nanocrystal size of 2.6 nm;
[0063] The second sputtering conditions are: using unbalanced magnetron sputtering technology, the pressure is 3×10 -3 Pa, substrate pulse bias voltage is -70 V, frequency is 250 kHz, argon pressure is 0.2 Pa, power of tungsten carbide target is 240 W, power of carbon target is 2500 W;
[0064] (3) A friction test was conducted using a CSM reciprocating friction and wear tester produced by Anton Paar, and a friction dual material ball was used to perform friction treatment on the surface of the WC / aC film obtained in step (2) to stimulate the WC nanocrystals to undergo an oxidation reaction to form WO 3 , and simultaneously drive WO 3 The sieve migrated to the surface of the dual steel ball and spontaneously constructed a WO-rich 3 Transfer film, thereby constructing a sliding interface with low shear force and weak adhesion characteristics, and realizing the regulation of the friction coefficient of the carbon-based film through friction-induced sliding interface reconstruction;
[0065] The friction dual material ball is a GCr15 ball with a roughness of 0.1 μm, a Rockwell hardness of 62, and a diameter of 6 mm;
[0066] During the friction treatment process, with the help of a high-precision atmosphere control system, the oxygen partial pressure in the environment is adjusted to 21% (air atmosphere), the temperature of the friction system is strictly controlled at 25° C., the relative humidity of the environment is adjusted to 30%, the load is maintained at 10N, the sliding frequency of the friction dual material ball is adjusted to 5Hz, the sliding reciprocating distance of the friction dual material ball is 5mm, and a constant load loading mode is adopted to achieve WO 3 The effective screening transfer; the friction treatment time is 30min, ensuring the rich WO 3 The continuity and integrity of the transfer film formation.
[0067] Embodiment 3, 4
[0068] A WC / aC film was prepared and its friction coefficient was adjusted according to the method of Example 2. The difference from Example 2 is that during the friction treatment process, the loads of Example 3 and Example 4 were controlled at 15N and 20N, respectively.
[0069] Comparative Examples 2 and 3
[0070] A WC / aC film was prepared and its friction coefficient was adjusted according to the method of Example 2. The difference from Example 2 is that during the friction treatment process, the loads in Comparative Examples 2 and 3 were controlled at 1N and 5N, respectively.
[0071] The tribological behavior of the WC / aC film during the friction treatment process described in Examples 2 to 4 and Comparative Examples 2 and 3 was tested using a CSM reciprocating friction and wear tester produced by Anton Paar, and the corresponding friction coefficient change trend diagram was obtained as shown in the figure: Figure 2 As shown, Figure 2 The small and medium figures are the corresponding curves of load and average friction coefficient. Figure 2It can be seen that the friction coefficient of the WC / aC film under the load of 10N described in Example 2 can reach 0.04, and the friction coefficients of Examples 3, 4 and Comparative Examples 2 and 3 reach 0.04, 0.07, 0.08 and 0.06 respectively. During the friction treatment process, the friction coefficient of the WC / aC film under the load described in Examples 2 to 4 and Comparative Examples 2 and 3 drops sharply after a short running-in period and reaches stability. Under the load of 10N described in Example 2, a uniform and dense WO-rich surface is formed on the surface of the dual steel ball rubbed with the WC / aC film with a WC nanocrystal size of 2.6nm. 3 Transfer film.
[0072] Example 5
[0073] A method for regulating the friction coefficient of a carbon-based film by friction-induced sliding interface reconstruction, comprising the steps of:
[0074] (1) AISI 304 stainless steel substrates were machined into 30 mm × 30 mm × 3 mm sizes and then polished with different grades of diamond paste to obtain a surface roughness Ra of 0.03 μm. They were then ultrasonically degreased with acetone for 15 min and heated with Ar at a substrate pulse bias of -500 V. + The ions were cleaned for 20 minutes to obtain a pretreated substrate, and then a first sputtering was performed to deposit a transition metal intermediate layer Cr layer with a thickness of 210 nm on the surface of the pretreated substrate;
[0075] The first sputtering conditions are: using unbalanced magnetron sputtering technology, the pressure is 3×10 -3 Pa, substrate pulse bias voltage is -70 V, frequency is 250 kHz, argon pressure is 0.2 Pa, and power of Cr target is 800 W;
[0076] (2) performing a second sputtering on the surface of the Cr intermediate layer obtained in step (1) to deposit a WC / aC film having a thickness of 2.3 μm and a WC nanocrystal size of 2.6 nm;
[0077] The second sputtering conditions are: using unbalanced magnetron sputtering technology, the pressure is 3×10 -3 Pa, substrate pulse bias voltage is -70 V, frequency is 250 kHz, argon pressure is 0.2 Pa, power of tungsten carbide target is 240 W, power of carbon target is 2500 W;
[0078] (3) A friction test was conducted using a CSM reciprocating friction and wear tester produced by Anton Paar, and a friction dual material ball was used to perform friction treatment on the surface of the WC / aC film obtained in step (2) to stimulate the WC nanocrystals to undergo an oxidation reaction to form WO 3, and simultaneously drive WO 3 The sieve migrated to the surface of the dual steel ball and spontaneously constructed a WO-rich 3 Transfer film, thereby constructing a sliding interface with low shear force and weak adhesion characteristics, and realizing the regulation of the friction coefficient of the carbon-based film through friction-induced sliding interface reconstruction;
[0079] The friction dual material ball is a GCr15 ball with a roughness of 0.1 μm, a Rockwell hardness of 62, and a diameter of 6 mm;
[0080] During the friction treatment process, the oxygen partial pressure in the environment is adjusted to 21% (air atmosphere) by means of a high-precision atmosphere control system, the temperature of the friction system is strictly controlled at 25° C., the relative humidity of the environment is adjusted to 5%, the load is maintained at 10N, the sliding frequency of the friction dual material ball is adjusted to 5Hz, the sliding reciprocating distance of the friction dual material ball is 5mm, and a constant load loading mode is adopted to achieve WO 3 The effective screening transfer; the friction treatment time is 30min, ensuring the rich WO 3 The continuity and integrity of the transfer film formation.
[0081] Embodiments 6 to 9
[0082] The WC / aC film was prepared and its friction coefficient was adjusted according to the method of Example 5, except that during the friction treatment process, the relative humidity of the environment in Examples 6 to 9 was adjusted to 10%, 20%, 30% and 40%, respectively.
[0083] The tribological behavior of the corresponding WC / aC films in Examples 5 to 9 during the friction treatment process was tested using a CSM reciprocating friction and wear tester produced by Anton Paar, and the corresponding friction coefficient variation trend diagram was obtained as shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the friction coefficient of the WC / aC film at the humidity of 5% RH described in Example 5 can reach 0.03, and at the humidity conditions described in Examples 6, 7, 8 and 9, it reaches 0.04, 0.05, 0.06 and 0.07 respectively. During the friction treatment process, the friction coefficient of the WC / aC film at the humidity conditions described in Examples 5 to 9 dropped sharply after a short running-in period and reached stability. At the humidity of 5% RH described in Example 5, a uniform and dense WO-rich surface was formed on the surface of the dual steel ball rubbed with the WC / aC film with a WC nanocrystal size of 2.6 nm. 3 Transfer film.
[0084] The tribological behavior of the WC / aC film in Example 5 during the friction treatment process was tested using a CSM reciprocating friction and wear tester produced by Anton Paar, and a three-dimensional morphology of the wear spot on the surface of the GCr15 ball was obtained. Figure 4 As shown by Figure 4 It can be seen that the wear spot surface of GCr15 ball is covered with obvious WO 3 The transfer film shows that the dual contact surface of the film is no longer the surface of the GCr15 ball, but the WO covered on the wear spot surface of the GCr15 ball. 3 Transfer film, forming carbon / WO 3 Transfer film-slide interface.
[0085] Figure 5 is a cross-sectional SEM image of the WC / aC film in Example 1 of the present invention, Figure 6 is a surface SEM image of the WC / aC film in Example 2 of the present invention, Figure 5 and Figure 6 It can be seen that a Cr intermediate layer is deposited on the AISI 304 stainless steel substrate, and then a WC / aC film with a thickness of 2.3 μm is deposited on the surface of the Cr intermediate layer, in which the size of the WC nanocrystals is 2.7 nm.
[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for regulating the friction coefficient of a carbon-based film by friction-induced sliding interface reconstruction, characterized in that: The following steps are involved: (1) pre-treating the substrate, and then performing a first sputtering to deposit a transition metal intermediate layer on the surface of the pre-treated substrate; (2) using carbon and transition metal carbide as sputtering targets respectively, performing a second sputtering on the surface of the transition metal intermediate layer obtained in step (1) to obtain a transition metal carbide reinforced carbon-based film; (3) A friction dual material ball is used to perform friction treatment on the surface of the transition metal carbide reinforced carbon-based film obtained in step (2), so as to stimulate the transition metal carbide nanocrystals to undergo an oxidation reaction to form oxidation products, and simultaneously drive the oxidation products to sieve and migrate, spontaneously construct a transition metal oxide transfer film, thereby constructing a sliding interface with low shear force and weak adhesion characteristics, and realizing the regulation of the friction coefficient of the carbon-based film by friction-induced sliding interface reconstruction.
2. The method according to claim 1, characterized in that The pretreatment in step (1) comprises: polishing the substrate, ultrasonic degreasing and Ar + Ion cleaning is performed to obtain a pretreated substrate.
3. The method according to claim 1, characterized in that In the step (1), the transition metal intermediate layer is a Cr or Ti layer; the thickness of the transition metal intermediate layer is 180 to 240 nm.
4. The method according to claim 1, characterized in that: In the step (2), the transition metal carbide is at least one of tungsten carbide and titanium carbide.
5. The method according to claim 1, characterized in that The conditions for the second sputtering in step (2) are: using unbalanced magnetron sputtering technology, the pressure is 2×10 -3 ~5×10 -3 Pa, the substrate pulse bias is -50 to -100 V, the frequency is 200 to 350 kHz, the argon pressure is 0.1 to 0.6 Pa, the power of the transition metal carbide target is 0 to 500 W, and the power of the carbon target is 1500 to 2500 W.
6. The method according to claim 1, characterized in that The thickness of the transition metal carbide reinforced carbon-based film in step (2) is 2-3 μm, and the average particle size of the transition metal carbide nanocrystals in the transition metal carbide reinforced carbon-based film is 1-10 nm.
7. The method according to claim 1, characterized in that In the step (3), the friction dual material ball is a GCr15 ball or an Al2O3 ball; the roughness of the friction dual material ball is 0.05-0.2 μm; and the Rockwell hardness of the friction dual material ball is 60-80.
8. The method according to claim 1, characterized in that During the friction treatment in step (3), the oxygen partial pressure in the environment is 20% to 50%, and the relative humidity of the environment is 5% to 50%; the temperature of the friction system of the friction treatment is 20 to 35°C.
9. The method according to claim 1, characterized in that: The load of the friction treatment in step (3) is 10 to 15N.
10. The method according to claim 1, characterized in that During the friction treatment in step (3), the sliding frequency of the friction dual material ball is 1 to 7 Hz, the sliding reciprocating distance of the friction dual material ball is 3 to 7 mm, and the friction treatment time is 30 to 60 min.
Citation Information
Cited By
Ultrasonic enhanced tribochemical catalysis film forming method
CN120666319A